A Triangulation Study to Assess the Perceived City Image in the Arab Middle East Context: The Case of Al-Ain in the UAE. Issue 2 (4th March 2018) - Eid, Riyad; Elbanna, Said
ABSTRACT: The study of city image has become a subject of increasing interest to researchers and practitioners. However, although many studies have found that success of an area's tourist development depends crucially on its image, most of studies concentrate on only a few destinations in the United States and the European Union, neglecting most emerging tourist destinations such as these in fuel-exporting countries. In order to fill this gap, this study adopted a two-stage design seeking to develop and test a scale of Perceived City Image (PCI) in a non-western context. In Stage 1, the authors; through a qualitative study, generated and refined the scale elements, recognizing unique characteristics of Al Ain. In Stage 2, the scale, through a quantitative study, has been assessed in terms of dimensionality, validity, and reliability. The overall results reflect appropriateness of the proposed constructs and provide an integrated perspective of PCI constructs in the Arab Middle East, where very little research can be found. Results, contributions, limitations, directions for future research, and managerial implications are all discussed.